How does foreign trade affect green total factor energy efficiency? Evidence from China - Xu, Jun; Li, Jinye; Liu, Chunyan (Frontiers in Environmental Science, 2022)
As the largest trading nation in the world, there have been substantial foreign trades (export and import) between China and other countries. Meanwhile, it is also one of the major forces for China’s emission reduction. This article applies the panel data of 30 provinces for the period 2004–2017 to investigate the effect of foreign trade on China’s green total factor energy efficiency (GTFEE). The slack-based measure (SBM) model is employed to calculate the provincial GTFEEs. Subsequently, the empirical results of the basic linear regression model revealed that both export and import promoted the region’s GTFEE, on which the import particularly has more effects than the export. Moreover, the spatial Durbin model (SDM) exhibited that the increase in import will not only present a positive influence on the GTFEE of the region, but also will improve the GTFEEs of the surrounding provinces through the spatial spillover mechanism. Although the increase in export will also exert a positive influence on the GTFEE of the local area, it will impose a significant negative impact on the GTFEEs of the surrounding regions. The results of this study provide important policy implications for the optimization of trade structure and high-quality development of the Chinese economy.